Marxism and feminism: 40 years of controversy - D ́Atri, Andrea (Pontifícia Universidade Católica de São Paulo, 2011)
This article addresses the debate between Feminism and Marxism, with an emphasis on radical Feminism, which, since the 1970’s, has helped guide the discussions on the emancipation of women. It is from a Trotskist standpoint, that we will address the contradictions of this current of thought and reaffirm the need for a social revolution as a condition to overcome the exploitation of workers and, in particular, of the female gender.